Metode Hermeneutika dan Implementasinya dalam Menafsirkan Alquran - Abdul Rasyid Ridho (Institut PTIQ Jakarta, 2017)
ooking at the times, humanitarian problems have grown so complex, ranging from genetic problems, space exploration, edu- cation, interreligious relationships, gender issues, human rights, and so on. The complexity of these developments is heavily influenced by the technology that has made everyone around the world interact easily and is not sealed by geography and time limits. The rapid de- velopment of the era makes the sciences of Islam unavoidably must follow the current era, and without exception the science of inter- pretation. Science of interpretation is required to always grow in the face of the complexity of humanity issues. Here then the idea of the use of hermeneutics born of “another world” becomes a necessity for the present interpreters. Hermeneutics as a methodology in the in- terpretation of the Qur’an is considered quite important and urgent to do because hermeneutics not only speak in the text only but also consider the context and role of subjectivity of an interpreter, so, by using this method, interpretation or study of the Qur’an is expected to be contextually actual contextual and answer the challenges of the times.